Orbit - Orbit Resonance of Pluto and Neptune (Global Journal of Science Frontier Research, 2012)
In the present paper, an algorithm for the planar restricted circular threebody problem in rotating symbolic system is developed to determine orbit-orbit resonance of Pluto and Neptune.
Keywords: Celestial Mechanics-Planetary close encounters-Pluto- Neptune- solar system dynamics